Life course exposure to smoke and early menopause and menopausal transition. Issue 10 (October 2015) - Tawfik, Hebatullah; Kline, Jennie; Jacobson, Judith; Tehranifar, Parisa; Protacio, Angeline; Flom, Julie D.; Cirillo, Piera; Cohn, Barbara A.; Terry, Mary Beth
Abstract Objective: Early age at menopause is associated with increased risk of cardiovascular disease, stroke, osteoporosis, and all-cause mortality. Cigarette smoke exposure in adulthood is an established risk factor for earlier age at natural menopause and may be related to age at the menopausal transition. Using data from two US birth cohorts, we examined the association between smoke exposure at various stages of the life course (prenatal exposure, childhood exposure to parental smoking, and adult smoke exposure) and menopause status in 1, 001 women aged 39 to 49 years at follow-up. Methods: We used logistic regression analysis (adjusting for age at follow-up) to estimate odds ratios (ORs) and 95% confidence intervals (CI) relating smoke exposure to natural menopause and the menopausal transition. Results: The magnitudes of the associations for natural menopause were similar but not statistically significant after adjustment for confounders among (i) women with prenatal smoke exposure who did not smoke on adult follow-up (OR, 2.7; 95% CI, 0.8-9.4) and (ii) current adult smokers who were not exposed prenatally (OR, 2.8; 95% CI, 0.9-9.0). Women who had been exposed to prenatal smoke and were current smokers had three times the risk of experiencing earlier natural menopause (adjusted OR, 3.4; 95% CI, 1.1-10.3) compared with women without smoke exposure in either period. Only current smoking of long duration (>26 y) was associated with the timing of the menopausal transition. Conclusions: Our data suggest that exposure to smoke both prenatally and around the time of menopause accelerates ovarian aging.